Brutalization and the Civilizing Process: An Ongoing Debate Between Mosse and Elias. (October 2021) - Benadusi, Lorenzo
The objective of this article is to compare the concept of brutalization, analyzed by George Mosse, with the civilizing process, described by Norbert Elias. The intellectual life of these German-Jewish scholars will be reconstructed through the study of their relationships and their similar life experience. In this way, I'll try to demonstrate that the apparent contrast between their different points of view is much more nuanced. Civilization and brutalization were not opposed processes that excluded one another. Therefore, a clearer understanding of the Great War can be best achieved through a combined reading of these two interconnected processes; and it is only by examining their interaction that we can understand the postwar period and the rise of Fascism and Nazism more fully.